STUDI TENTANG FAKTOR-FAKTOR PENGHAMBAT PROSES BELAJARMENGAJAR BAHASA INGGRIS DI KELAS II SMPN 1 KUTA UTARA DAN SMP BUDI UTAMA KEROBOKAN BERDASARKAN KURIKULUM 2004 - Ni Nyoman Yuliantini (Politeknik Negeri Bali, 2013)
This study was answering some questions about the obstacles encountered by the students in studying English, concerning motivation and support by the parents for their children in studying English, the constraints faced by the English teachers at school and the conditions of English teaching facilities and other supports. On the basis of data processing and analysis the following conclusion can be drawn: (a) The students face any significant obstacles. Although most of them admitted that English was difficult subject, they said that their English was good enough. (b) On the whole, their parents gave their children not enough motivation. However, the facilities for the teaching and learning were not adequate. (c) Not all of the teachers had a syllabus, 4 out 6 of the respondents said that they had difficulty in understanding and translating general educational objectives into specific educational objectives. All of the teachers had English education background. However,experiences in participating in training on the teaching and learning process and syllabus were insufficient. (d) All of the school had libraries, but they had not yet had language laboratory facilities (they were still making an effort to make them available).